Peramalan Jumlah Produksi Kayu Manis di Sumatera Barat dengan Metode Pemulusan Eksponensial Tripel Tipe Brown - Athifah Rahmi; Helma Helma; Riry Sriningsih (Journal of Mathematics UNP, 2018)
Abstract - Cassiavera in West Sumatra is part of the plantation sector, which provides largest export value to local revenue. However, in 2006-2015 the total of cassiavera’s production of West Sumatra has decreased fluctuation. Therefore it is necessary to estimate the amount of cassiavera production in future. The purpose of study was to determine total’s mode of cassiavera’s  production in West Sumatra, Kab. Tanah Datar and Kab. Agam and know the results of the forecast production quantities of  cassiavera. The data used is BPS data’s in Padang city 2006-2015. The method used is the method of Triple Exponential Smoothing Brown mode with parameter α. When setting parameter α then used MSE (Mean Square Error). The results of the forecast production total of cassiavera in three regions in 2016-2020 sequentially in tonnes is 29531.88, 31505.98, 33869.79, 36623.31 and 39766.54; 2660.16, 2334.63, 1999.18, 1653.79 and 1298.47; 4783.84, 4652.65, 4518.58, 4381.63 and 4241.81.